Analysis of Compaction Quality of Class A Aggregate Base Using the Sand Cone Method on the Teluk Tapang Port Access Road - Evince Oktarina; Tiva Maizar Lina (Universitas Putra Indonesia YPTK Padang, 2026)
This study, entitled “Analysis of Compaction Quality of Class A Aggregate Base Using the Sand Cone Method on the Teluk Tapang Port Access Road Project”, aims to evaluate the field compaction quality and its conformity with the applicable technical specifications. The research scope includes field data collection of moisture content and in-situ density on the Class A aggregate base layer at several test points along the access road alignment to Teluk Tapang Port. The method used is the Sand Cone Test in accordance with SNI 03-2827-2011, to determine the in-situ dry density of the compacted layer. The field density values were compared to the laboratory maximum dry density obtained from the Modified Proctor Test, to calculate the degree of compaction (% compaction). The data were analyzed descriptively to observe the relationship between moisture content and compaction level, as well as to evaluate compliance with Bina Marga standards, which require a minimum of 95% compaction for the upper base layer. The results from 60 test points show that the moisture content ranged from 1.32% to 17.7%, with an average of 7.49%, while the compaction percentage ranged from 51.19% to 99.70%, with an average of 86.15%. Evaluation results indicate that 46.7% of the test points achieved compaction above 90%, and only 21.7% met the 95% requirement set by Bina Marga standards. It can be concluded that the compaction quality of the Class A aggregate base layer on this project has not fully met the specified compaction standards, particularly at several stations with moisture content either above or below the optimum level. Therefore, better moisture control and compaction procedures are required to achieve more uniform and compliant results.